2016
DOI: 10.1080/00140139.2015.1132013
|View full text |Cite
|
Sign up to set email alerts
|

Optimal fall indicators for slip induced falls on a cross-slope

Abstract: Slip-induced falls are among the most common cause of major occupational injuries in the UK as well as being a major public health concern in the elderly population. This study aimed to determine the optimal fall indicators for fall detection models which could be used to reduce the detrimental consequences of falls. A total of 264 kinematic variables covering three-dimensional full body model translation and rotational measures were analysed during normal walking, successful recovery from slips and falls on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…As expected, F x has a huge change with the change of the cross‐slope angle, while F y and F z have a small change, considering that the change of the cross‐slope angle of the pavement is mainly in the lateral change. At the same time, it can be seen that the occurrence time of the extreme value of GRF with the increase of the cross‐slope angle which may be due to the increase of the cross‐slope angle that changes the gait of subjects [23], leads to a decrease in speed, which then leads to the time lag of the occurrence of GRF extreme value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, F x has a huge change with the change of the cross‐slope angle, while F y and F z have a small change, considering that the change of the cross‐slope angle of the pavement is mainly in the lateral change. At the same time, it can be seen that the occurrence time of the extreme value of GRF with the increase of the cross‐slope angle which may be due to the increase of the cross‐slope angle that changes the gait of subjects [23], leads to a decrease in speed, which then leads to the time lag of the occurrence of GRF extreme value.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pavements often have intermittent cross‐slopes, previous research has indicated an increased number of slips occurring on cross‐slope than on flat surface, was postulated to be due to the reduced normal force acting on the foot requiring a higher friction to avoid a slip [19]. Due to the asymmetrical demands of cross‐slope walking this introduced functional balance barriers, led to reduced step width [20], increased foot‐floor plantar flexion angles [21], increased plantar support areas [22] and decreased the average speed of walking [23]. Further, a study involving ground reaction forces (GRF) showed that the peak of the force occurred earlier when walking on the level than on the cross‐slope pavement [24].…”
Section: Introductionmentioning
confidence: 99%